KfW/ZEW CO2 Barometer 2014 – Manufacturing Industry Edition: Rising energy costs and more competition - drivers for investment in energy efficiency? - Karl Ludwig Brockmann; Caroline Dieckhöner; Carlo Gallier; Benjamin Lutz (KfW Bankengruppe und Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
As a complementary study, KfW Bankengruppe and the ZEW have developed a second annual survey in the framework of the KfW/ZEW-CO2-Barometer: the KfW/ZEW-CO2-Barometer – Manufacturing Industry Edition. The aim is to shed light on recent developments in the German manufacturing industry driven by European climate and energy regulations as well as the German energy transition in particular. The survey covered topics concerning energy price expectations, investments in energy efficiency and the German energy transition. Main Results of the Survey: Energy Efficiency Assessments Are a Prerequisite for Investments in Energy Efficiency. Companies Expect Increasing Energy Prices and their Most Important Sales Markets to Be Global. Half of the Companies Use Energy Consulting Services. Energy Contracting Is Being Used only by a Minority. Grid Expansion is Still Considered as the Major Challenge of the German Energy Transition.
Keywords: 330